Priority Analysis of It Users Needs By Utilizing DSS Tools As A Suggested Material In The Early Development Of It Strategic Plan University Technology Of Yogyakarta - Hariadi Dodi (International Journal of Applied Business and Information Systems, 2018)
Organizations that use information technology in conventional and do not have confirmed information technology planning will be left behind by its competitors. Numerous studies illustrate the negative consequences of the absence of the IT strategy. Although important, it is believed many organizations do not have it. Likewise University of Technology Yogyakarta (UTY), an organization engaged in education. This paper begins by determining the priority needs of users of IT, then combine with environmental conditions and SWOT analysis of information technology to be analyzed and aligned with strategic business planning UTY. Researchers use DSS (Decision Support System) tools to facilitate in determining the priority needs of users. This research resulted in the proposed initial development of IT Strategic Plan in accordance with business strategy UTY. With the approach to the priority needs of users of IT then IT Strategic Plan can be realized immediately. This is according to the organization that did not have the IT Strategic Plan.